Rancang Bangun Sistem Informasi Montir Berbasis Website di Bangkinang Kota (Programming) - Akbar, Syahidul; Munti, Novi Yona Sidratul; Musridho, Raja Joko (PT Pustaka Cendekia Group, 2023)
Today, information technology is growing. With the existence of information systems in various fields of companies and other industries, making a company/industry develop. The application of information systems in automotive is important to support data processing, transactions, and easily computerized report generation. In general, Mechanic is a person who has expertise in repairing and installing motorized vehicle engines. According to Arief (2011:7), In writing this final project, the author conducted research in the Bangkinang City area, Bangkinang Kota District, Kampar Regency, Riau Province. To conduct research on the data needed in the mechanic selection process, qualitative methods are used. With this method, interviews and direct observations were conducted. The method used in the development of this system is a prototype. The implementation has 3 parts, namely databaseimplementation, system implementation, and system testing. The test method used is the direct test method, namely blackbox testing. Based on the results obtained from a series of research processes, it can be concluded that: This information system can provide fast and accurate information needed by customers. With the creation of a website it can help and facilitate the community especially motor vehicle users in carrying out service.